Developing a Competency Standard for TVET Teacher Education in Asean Countries - Michael Grosch (Faculty of Engineering, Universitas Negeri Yogyakarta, 2017)
Most ASEAN member countries are currently facing a lack of skilled labor which is jeopardizing their further economic development. To tackle this issue, it is crucial to improve the Technical and Vocational Education and Training (TVET) system, in which the quality of TVET teachers constitutes a main key factor. Establishing an International mutual TVET Teacher Master program and degree for ASEAN countries can enhance TVET teachers’ competence in the ASEAN community. The paper presents a competency framework for TVET teachers in ASEAN countries that was developed by a focus group from five ASEAN countries during two workshops from 2015 to 2016, which can be used as a blueprint for setting up such an international TVET Master program for the ASEAN community. The paper also elaborates further steps to be conducted to set it into practice.